EXIT25 - Executive interview applied to a cognitively healthy elderly population with heterogeneous educational background - Maria Niures P.S. Matioli; Paulo Caramelli; Bárbara D. Marques; Fernanda D. da Rocha; Maria Cristina C. de Castro; Samia R. Yamashita; Alberto de M. Soares (Dementia & Neuropsychologia)
Abstract Education interferes with the performance in most cognitive tests, including executive function assessment. Objective: To investigate the effects of education on the performance of healthy elderly on the Brazilian version of the Executive Interview (EXIT25). Methods: The EXIT25 was administered to a sample of 83 healthy elderly. The subjects were also submitted to the Mini-Mental State Examination (MMSE), a delayed recall test, clock drawing and category fluency (animals/min) tests in order to rule out cognitive impairment. The Geriatric Depression Scale (GDS) was employed to exclude clinically-relevant depressive symptoms. The total sample was divided into three groups according to educational level: G1 (1-4 years), G2 (5-8 years) and G3 (>8 years). Results: The mean values for age, educational level, MMSE and EXIT25 scores of all subjects were 72.2, 7.5, 27.6 and 6.9, respectively. The scores on the EXIT25 for each group were: G1=8.3, G2=5.9 and G3=5.8. There was a statistical difference between the performance of G1 and the other two groups on the EXIT25. Conclusions: The Brazilian version of the EXIT25 proved straightforward to administer. The performance of this sample of healthy elderly on the test was significantly influenced by educational level.